Physicochemical features of rivers and lakes in pantanal wetland - Saijo, Yatsuka; Mitamura, Osamu; Hino, Kozo; Ikusima, Isao; Tundisi, José Galizia; Matsumura-Tundisi, Takako; Sunaga, Tetsuo; Nakamoto, Nobutada; Fukuhara, Haruo; Barbosa, Francisco Antonio R.; Henry, Raoul [UNESP]; Silva, Vangil Pinto (The Japanese Society of Limnology, 1997)
The Pantanal is one of the largest wetland in the world, and its located almost in the central part of South America. Preliminary studies on the chemical features of waters were carried out in July, 1983 in Rio Paraguai and its tributaries in southern Pantanal, and in January, 1986 for some lakes near Porto Jofre and a river in northern Pantanal. The former showed an extremely oligotrophic character and the latter a eutrophic character, while the nitrogen seemed to be the limiting nutrient rather than phosphorus in both waters. The oxygen deficiency in water seemed rather common throughout the area studied in spite of the difference in water temperature and the organic matter contents.
Keywords: Dissolved oxygen; Nutrient; Organic matter; Pantanal wetland